Influence of Polyethylene Glycol Lipid Desorption Rates on Pharmacokinetics and Pharmacodynamics of siRNA Lipid Nanoparticles - Barbara L Mui; Ying K Tam; Muthusamy Jayaraman; Steven M Ansell; Xinyao Du; Yuen Yi C Tam; Paulo JC Lin; Sam Chen; Jayaprakash K Narayanannair; Kallanthottathil G Rajeev; Muthiah Manoharan; Akin Akinc; et al. (Elsevier, 2013)
Lipid nanoparticles (LNPs) encapsulating short interfering RNAs that target hepatic genes are advancing through clinical trials, and early results indicate the excellent gene silencing observed in rodents and nonhuman primates also translates to humans. This success has motivated research to identify ways to further advance this delivery platform. Here, we characterize the polyethylene glycol lipid (PEG-lipid) components, which are required to control the self-assembly process during formation of lipid particles, but can negatively affect delivery to hepatocytes and hepatic gene silencing in vivo. The rate of transfer from LNPs to plasma lipoproteins in vivo is measured for three PEG-lipids with dialkyl chains 14, 16, and 18 carbons long. We show that 1.5 mol % PEG-lipid represents a threshold concentration at which the chain length exerts a minimal effect on hepatic gene silencing but can still modify LNPs pharmacokinetics and biodistribution. Increasing the concentration to 2.5 and 3.5 mol % substantially compromises hepatocyte gene knockdown for PEG-lipids with distearyl (C18) chains but has little impact for shorter dimyristyl (C14) chains. These data are discussed with respect to RNA delivery and the different rates at which the steric barrier disassociates from LNPs in vivo.